An experimental study of CaSO4 decomposition during coal pyrolysis. (1st January 2016) - Jia, Xin; Wang, Qinhui; Cen, Kefa; Chen, Leming
Graphical abstract: Highlights: The coal strongly enhanced CaSO4 decomposition during pyrolysis. The solid–solid reaction mechanisms could provide a better explanation for CaSO4 decomposition during pyrolysis. The inherent minerals of coal could promote CaSO4 decomposition. CaSO4 decomposition rate was significantly decreased with the increase of coal particle size. Abstract: Coal with different proportions of CaSO4 was pyrolyzed in a fixed-bed reactor in a temperature range of 500–800 °C to study the mechanism of CaSO4 decomposition during coal pyrolysis. The results showed that the presence of coal could greatly promote CaSO4 decomposition at high temperatures, and 87% CaSO4 was decomposed at 800 °C during Xiaolongtan lignite pyrolysis, which was mainly attributed to the solid–solid reaction (2C + CaSO4 → CaS + 2CO2 ). The effects of inherent minerals, coal type, holding time and coal particle size on CaSO4 decomposition were also discussed. By comparing the CaSO4 decomposition rate between raw coal and demineralized coal, it could be concluded that the inherent minerals could greatly enhance CaSO4 decomposition at high temperatures, which was also be proved by the results of thermogravimetric analysis (TGA). CaSO4 decomposition rate presented a significant decrease with the increase of coal particle size. Four coals used in this study could all promote CaSO4 decomposition, but the promotion effect differed among those four coals which may be attributed to the difference in inherent minerals and the reactivity of coal.